Nombrar la muerte: la labor de los funcionarios forenses y acompañantes psicológicos durante la restitución de cuerpos en el proceso de búsqueda humanitaria en Ayacucho en 2023 - Jarufe Caballero, Mauricio; Macassi Orellana, Nicoll (Pontificia Universidad Católica del Perú, 2025)
Under a qualitative-ethnographic methodology, this paper reports the findings obtained during fieldwork practice held in May, 2023 in Ayacucho Perú, as part of the Anthropology program at the Pontificia Universidad Católica del Perú. This paper describes the work of forensic officials and psychological companions during the restitution of human remains of victims from the Internal Armed Conflict in Perú, as well as the relations established with the families of the disappeared. This paper includes ethnographic data gathered from participant observation during the anatomical assemblage of the remains and the official ceremony of restitution, as well as data from semi-structured interviews with State officials, NGO associates and relatives of the returned disappeared persons.We frame the restitution process as a series of actively politicized events that display State-imposed narratives of closure and reparation, further affecting the mourning of the victims and their relation with the State. We analyze the symbolic dimension of the anatomical assemblage, describing the embodiment of the disappeared being, the multiple ontologies of human remains and the different forms of mourning that arise from them. Due to the conditions previously described, we conclude that forensic officials and psychological companions adopt different strategies to legitimize their work in the interactions with the families of the disappeared, and the way their own perspectives on death and restitution affect these relations.

Siguiendo un enfoque cualitativo-etnográfico, el artículo presenta los hallazgos obtenidos durante el curso de Práctica de Campo 1 de la carrera de Antropología en la Pontificia Universidad Católica del Perú, realizada en mayo de 2023 en Ayacucho, Perú. Se escribe y analiza la labor de los funcionarios y acompañantes en el proceso de restitución de cuerpos y la relación que estos establecen con familiares de personas desaparecidas durante el Conflicto Armado Interno en el Perú. Los datos provienen de la observación participante en el armado anatómico de los cuerpos exhumados y en la ceremonia de restitución, así como de entrevistas con funcionarios forenses, acompañantes psicológicos y familiares de los desaparecidos. Se analiza el proceso de restitución como una serie de eventos politizados que presentan la narrativa estatal sobre la restitución, los cuales afectan la forma en que los familiares afrontan el duelo y se relacionan con el Estado. Se analiza la dimensión simbólica del armado de cuerpos, el proceso de corporización del sujeto desaparecido, las distintas ontologías de cuerpos exhumados y los distintos duelos producidos en este proceso. Asimismo, se analizan las estrategias utilizadas por funcionarios y acompañantes para relacionarse con los familiares, y cómo las percepciones en torno a la muerte y a la restitución afectan estas formas de relacionarse.
Naming death: the labor of forensic officials and psychological counselors during the restitution of bodies in the humanitarian search process in Ayacucho in 2023
Keywords: Ayacucho; Restitution; Death; Post-conflict; Body accompaniment; Ayacucho; Restitución; Muerte; Postconflicto; Acompañamiento; https://purl.org/pe-repo/ocde/ford#5.04.03